Translation and propaganda: a historical insight into the 20th century dictatorship in Portugal - Chumbo, Isabel (2018)
This contribution is about the relation between translation and propaganda and concerns translation as a means of promoting influence abroad in the context of the 20th century Portuguese dictatorship. The study will focus on the way the regime organized itself around translation in the period from 1933 to 1950 and how this topic was addressed mainly through the propagandistic discourse contained in the English speeches by dictator António Oliveira Salazar. So far, research has mainly paid attention to translated literature into Portuguese, but this proposal discusses the issue from the inverse perspective, allowing us to perceive what happened from within the regime, specifically concerning the translation of speeches into English. The publication of the book Doctrine and Action by Faber and Faber at the beginning of the 2nd World War, as well as other speeches, appears to be motivated by the need to convince the British of a positive, although politically neutral position in the conflict and by the need to distance Portugal from the Spanish intervention and conflicts of the time. The translation of these speeches can be viewed as a soft power attitude in those days and is mainly achieved through the comparative analysis of translation shifts, strategies and procedures, as well as a descriptive analysis. Thorough archival work allows the description of the process surrounding these translations, as well as the agents involved, namely the editor T. S. Eliot, responsible for the publishing of the aforementioned book. Several letters provide details into how the regime organized and viewed the purpose of translation in general and of these speeches in particular. The proposed study will allow a particular view into the sociological process of translation during Salazar’s dictatorship, but also a more focused view on a corpus of translated speeches, which can furnish valuable indications about the translation process.